Spore-Based Palynological Study of Common Pteridophyte Species in Cagraray Island, Philippines: Grounds for Classification in Lower Taxa - Barcenas, Jay Mar A.; Bechayda, Christine C. (International Journal of Scientific Research in Biological Sciences, 2022)
This mixed-design study aims to document the spore characteristics of common pteridophyte species in Cagraray Island, Philippines through palynology. This bridges the gap between spore-based palynological study and scheme for classifications in lower taxa of pteridophyte species. A total of 18 pteridophytes collected from three barangays in Cagraray Island were identified under eight distinct types of families. The spores from the fronds of pteridophytes were gathered and observed using compound microscope while its measurement was supervised by a micrometer. The study revealed three major spore shapes as to tetrahedral, tetrahedral-globose and ellipsoidal, whereas spore appendages were primarily spiny, longitudinally striate, globose, reticulate, angular, warted, and rugose/wrinkled. Sizes of spore vary from 32.67µm to 34.32µm showing parallelism from the majority of previously documented works with significant and minimal changes in the spore size of other species. Classification in lower taxa following the spore shape and appendage was proposed as an augmentation for future classification of pteridophytes particularly under sub-genera and sub-families. This study concluded the variation in the morphological characteristics of pteridophyte spores and the abundance of genetic variety resulting into multiple arrays of pteridophyte spores’ characteristics. This study recommends the need to update the records on palynology research specifically in the characterization of spores of pteridophyte species. Future parallel investigations and studies are also recommended to other pteridophyte species not considered in the present research.